Prologue - Christoffersen, Erik Exe; Winkelhorn, Kathrine (Peripeti, 2017)
Hotel Pro Forma is a Copenhagen-based international laboratory for performing arts – a small production company with substantial influence on the performing arts in Scandinavia and Europe. Since 1985 Hotel Pro Forma has staged more than 50 productions shown in more than 30 countries around the world from New York, Sydney to Taipei. Productions are developed through an intensive period of research, and different themes are taken from a wide-ranging field of interest. This special English issue presents selected Hotel Pro Forma productions. Most readers will probably not have seen the performances, which is why we have been at pains to describe the different productions. We have selected those we consider to have influenced the performing arts the most by expanding the medium of the performing arts. Further we wanted to include a number of photos for the reader to get a more precise impression of Hotel Pro Forma’s pioneering works. Some of the articles have previously been published in Danish in: Skønhedens Hotel, Hotel Pro Forma, Et laboratorium for scenekunst, Aarhus University Press, 2015.